G Suite For Dummies - McFedries, Paul (--For dummies., 2020)
Get fast answers to y our G Suite questions with this friendly resource G Suite For Dummies is the fun guide to the productivity suite that's quickly winning over professional and personal users. This book shares the steps on how to collaborate in the cloud, create documents and spreadsheets, build presentations, and connect with chat or video. Written in the easy-to-follow For Dummies style, G Suite For Dummies covers the essential components of Google's popular software, including: Google Docs for word processing Gmail for email Google Calendar for scheduling and day planning Google Sheets for spreadsheet functionality Google Drive for data storage Google Hangouts and Google Meet for videoconferencing and calling capability The book helps navigate the G Suite payment plans and subscription options as well as settings that ensure your own privacy and security while operating in the cloud. Perfect for anyone hoping to get things done with this tool, G Suite For Dummies belongs on the bookshelf of every G Suite user who needs help from time to time.